Writing Disability in ADHD Children - François, Gaillard; Vincent, Quartier; Pascal, Roman (Journal of Organizational Psychology, 2021)
The psychological examination aims at objectifying the key symptoms of hyperactivity, i.e. attention and executive function disorders (in short, activation-inhibition control). The files of 237 patients from our consultations, aged between 5 and 17 years old and examined between 2004 and 2016, are analyzed retrospectively. Of whom 40 cases show the typical ADHD syndrome, mixed presentation, according to DSM-5 criteria. These ADHD children and adolescents show not only a characteristic impulsivity on computerized attention tests, but also a deficit in the acquisition of writing, an early manifestation of their neurodevelopmental disorders. This association correctly classifies 82.4% of hyperactives and controls, a strong effect given the difficult diagnosis of ADHD syndrome.